Investigation of intestinal parasitism among Hispanic migrant and seasonal farm workers in eastern North Carolina - Russell, Mindi (My University, 2007)
In collaboration between the North Carolina State Laboratory of Public Health (NCSLPH) and Dr. Maria T. Correa from the North Carolina State University College of Veterinary Medicine, the field experience focused on the development and application of accurate and rapid methods to detect and generally characterize Taenia solium in human stool samples. T. solium, the "pork tapeworm," is associated with cysticercosis in humans, is distributed worldwide, and the leading cause of adult-onset epilepsy. Approximately 90% of patients with cysticercosis develop nuerocysticercosis (NCC). NCC is endemic in most of Central and South America, and Asia. In the U.S., over 1,000 NCC cases are diagnosed each year, mostly in the immigrant population. In North Carolina, 192 cases of NCC have been diagnosed between 1995 and 2002. In initial studies, Multiplex PCR was used for the differential diagnosis of taeniasis, caused by T. saginate, T. asiatica and two genotypes of T. solium (Asian and American/African genotypes). This detection approach was evaluated on clinical (fecal) specimens submitted to NCSLPH for diagnostic purposes with the intent to expand screening to include a larger percentage of the immigrant populations.
Keywords: Intestional parasitism; Migrant farm workers; Emerging public health concerns; Food safety; Health and hygiene; Foodborne parasites; Adult on-set epilepsy; NCSLPH; Agriculture, Food Science and Technology (0359)